The concept, essence and role of student project activities and project management office placement in the structure of its management - A. I. Gromova; P. V. Pavlovsky (Вестник университета, 2023)
The article studies peculiarities of project activity organization in educational organizations of higher education. The relevance of the study is determined by higher education organizations’ interest in introducing and developing project activity and using concepts related to it. The concept of project is used by higher education organizations not in its direct meaning, but to reflect students’ practical activity. The article describes peculiarities of university-based project office functioning and their tasks. Justifications for involving third-party organizations such as outsourcing to implement functions of the upper management level of project management office have been given. The authors resort to scientific literature and other official sources that confirm correctness and validity of their arguments.